Implementation of Discharge Planning Based on Patient Centered Care for Post Stroke Patients in the Stroke Unit: A Systematic Review - Halimatus Sa’diyah; Mira Triharini; Ilya Krisnana; Novia Caecilia Laoli; Nurma Lindawati (Nusantara Medical Science Journal, 2026)
Background: Stroke is a major mortality factor necessitating coordinated care systems to prevent incidents and enhance patient prognosis. The implementation of discharge planning based on patient centered care in stroke patients aims to increase patient involvement through the provision of personalized information and shared decision making, in order to prepare patients for daily activities after discharge from the hospital. This study aims to Assess the effectiveness and impact of implementing patient-centered care-based discharge planning after stroke on patient satisfaction, quality of life, and reduction in hospital re-visits. Methods: The authors conducted a systematic review using PRISMA 2020 Guidelines. The article were derived from four electronic databases (Web of Science, JStor, PubMed, and Scopus) using keywords and terms relevant to the research topic. Consisting of full text original research articles published between 2019 and 2025 using quantitative and qualitative methods. Results: A total of 2,518 records were identified. Nine articles met the selection inclusion criteria were included due to having good methodological quality Patient-centered discharge planning interventions were associated with improved quality of life, patient satisfaction, adherence to post-discharge plans, and reduced hospital readmissions. Conclusion: Patient-centered discharge planning models positively influence patient satisfaction, quality of life, and rehospitalization rates among post-stroke patients. Implementing structured, multidisciplinary discharge planning protocols based on patient-centered care principles is crucial to improving stroke recovery outcomes.